Antiplasmodial and antigonococcal bioactivity of Tabernaemontana elegans stapf. (Apocynaceae) stem bark fractions - Bapela, Johanna (University of Pretoria, 2024)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2023.